SISTEM PENGELOLAAN BAHAN BAKU BERBASIS JUST IN TIME (JIT) PADA UMKM “ANEKA KERIPIK KARTINI” - Wiji Astuti; Isharijadi Isharijadi; Elana Era Yusdita (Politeknik Ubaya, 2022)
Abstract Just In Time is one of the planned techniques to obtain quality, control expenses and achieve timely delivery to consumers. The purpose of this study is to understand the raw materials management systems using Just In Time (JIT) on UMKM “ Aneka Keripik Kartini”. The method used was descriptive qualitative method. Data were obtained by interview, observation and documentation. Informants consisted of owners, suppliers, customers. The results of this study show that the purchase of raw materials for the production process of cassava and banana chips is carried out in Just In Time, the production process is based on ordering requests from consumere. The production pattern is corrugated where production is adjusted to product sales. When product orders increase, fulfill demand by ordering from other suppliers if the main supplier cannot meet demand.